Increased Expression of Prolyl Endopeptidase Induced by Oxidative Stress in Nucleus Pulposus Cells Aggravates Intervertebral Disc Degeneration - Huo-Liang Zheng (Oxidative Medicine and Cellular Longevity, 2022)
A healthy microenvironment of the intervertebral disc tissue is characterized by hypoxia owing to its sparse vascular distribution. Oxidative stress plays a pivotal role in the pathological development of intervertebral disc degeneration (IVDD). We found that the expression of prolyl endopeptidase (PREP) increased in degenerative nucleus pulposus (NP) tissues. The purpose of this study was to determine whether PREP is involved in oxidative-stress-induced IVDD. Tertbutyl hydroperoxide can inhibit the expression of PREP by activating the PI3K/AKT signaling pathway at low concentrations in NP cells. Knockdown of PREP protected NP cells from apoptosis induced by oxidative stress, whereas overexpression of PREP exacerbated the apoptosis of NP cells. We also investigated the connection between the PI3K/AKT signaling pathway and PREP and found that the activation of the PI3K/AKT signaling pathway downregulated the expression of PREP by inhibiting p53. As a crucial transcription factor, p53 binds to the PREP promoter region and promotes its transcription. Overexpression of PREP also impairs protein secretion in the extracellular matrix of NP cells. Furthermore, the in vivo knockout of PREP could attenuate puncture-induced IVDD. These findings suggested that the downregulation of PREP might maintain the viability of NP cells and attenuate IVDD under oxidative stress.